Function of major histocompatibility complex class II promoters requires cooperative binding between factors RFX and NF-Y. - Reith, W (1994)
Transcription of major histocompatibility complex (MHC) class II genes is controlled largely by the conserved promoter elements called the X and Y boxes. We show here that RFX, the X box-binding protein deficient in certain MHC class II-deficient immunodeficiency patients (CID), and the Y box-binding protein NF-Y bind cooperatively. Functional relevance of this protein-protein interaction is suggested by the fact that promoter activity correlates with cooperative binding of RFX and NF-Y rather than with binding of RFX or NF-Y alone. Stability of the RFX/NF-Y complex is affected by alterations in X-Y box spacing. These results are consistent with the fact that MHC class II promoter function is dependent on correct stereospecific alignment of the X and Y boxes. Cooperative binding involving RFX, NF-Y, and perhaps other MHC class II promoter-binding proteins may explain why the highly specific defect in binding of RFX observed in CID cells is associated in vivo with a bare promoter in which all of the cis-acting elements, including the X and Y boxes, are unoccupied.